Action of Light on Metabolism of Yeast FT-858 - Santos, Maria do Socorro Mascarenhas; Mueller, Larissa Pires; de Amorim, Murilo Gonçalves; Cardoso, Claudia Andrea Lima; Silva, Emilia Maria; Batistote, Margareth (Orbital: The Electronic Journal of Chemistry, 2019)
The light source can cause ultrastructural and morphological changes in yeast and affect your metabolism. Thus, this work has the objective of evaluating the influence of white and ultraviolet light on the fermentative performance of FT-858 yeast in different culture conditions. Yeast cells were grown in Yeast Extract-Peptone-Dextrose (YPD 2%) in which 0.10 g of yeast were added and incubated on a shaker for 10 h at 30 °C at 250 rpm, subsequently washed and centrifuged in solution saline. The biomass harvested was used in the fermentation experiments that were readily performed under white and ultraviolet light with temperature control. Aliquots were withdrawn for cell viability analysis and ethanol production. Yeast showed better performance under white light at 28 °Brix concentration at 30 °C. Ultraviolet light associated with high temperature and substrate concentration affected yeast physiology by directly interfering with viability and ethanol production. DOI: http://dx.doi.org/10.17807/orbital.v11i4.1219